PENINGKATAN MOTIVASI BELAJAR DALAM PEMBELAJARAN TEMATIK INTEGRATIF MELALUI TEKNIK REWARD SISWA KELAS V SD NEGERI 0 1 1 DESA BARU SIAK HULU - Mahermawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is a classroom action research conducted at SD Negeri 011 Baru Village, which is the background of this research is the low level of learning interest of 5th-grade students so that researchers improve the learning process by using reward techniques. The results of this study show that student learning interest has increased. This can be seen from the increase in learning motivation seen from the results of the classical student motivation scale on pre-action to get a percentage of 54.31%, the first cycle gets a percentage of 71.65% and the second cycle gets a percentage of 90.10% so that it has reached the criteria of success. Increased student learning motivation is seen from the average percentage of the results of individual student motivation learning scale, the number of students who meet the criteria of success in pre-action a number of 4 students or 8.35% students, the first cycle a total of 15 students or 31.25% students, cycle II a total of 45 students or 93.75% of students.